2005
DOI: 10.1111/j.0030-1299.2005.13082.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological subsystems via graph theory: the role of strongly connected components

Abstract: In this paper we investigate ecological flow networks via graph theory in search of the real sequential chains through which energy passes from producers to consumers in complex food webs. We obtain such fundamental pathways by identifying strongly connected components (SCCs), subsystems that groups species that take part in cycling, and performing topological sorting on the acyclic graphs that are obtained. Topological sorting identifies preferential directions for energy to flow from sources to sinks, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Their TðGÞ > 0 values indicate a certain degree of pyramidal structure and the low OðGÞs are consistent with an important role played by loops. The special status of these networks (not shared by other webs) is consistent with the well-known picture of a trophic pyramid combined with the presence of recycling (16,54).…”
Section: Null Models and Real Network Analysissupporting
confidence: 84%
“…Their TðGÞ > 0 values indicate a certain degree of pyramidal structure and the low OðGÞs are consistent with an important role played by loops. The special status of these networks (not shared by other webs) is consistent with the well-known picture of a trophic pyramid combined with the presence of recycling (16,54).…”
Section: Null Models and Real Network Analysissupporting
confidence: 84%
“…Computer programs can iteratively solve secondary extinctions, but this can be inefficient for large networks. A more sophisticated approach from graph theory is to use a depth-first search of the rooted network (Allesina et al 2005). Rooting a network involves assigning a basal species as a root node as a resource (Allesina et al 2009).…”
Section: Model Structurementioning
confidence: 99%
“…This measures the presence and strength of cyclic pathways in a strongly connected component (SCC) of a network. There has not been much application of SCC to ecosystems, but Allesina et al (2005a) recently demonstrated how one could decompose food webs into SCC to determine possible compartments. For an irreducible matrix, max is bounded by n. For a reducable matrix (several SCCs), max is bounded by the number of nodes in the largest subcomponent, and is the dominant eigenvalue for the subcomponent with the strongest degree of structural cycling.…”
Section: Structural Cyclingmentioning
confidence: 99%